PERFORMANCE IMPROVEMENT OF VENTURI WET SCRUBBER - devi S, Kousalya; S, Mr.Venkatesh; Chandrasekaran, Mr. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Environmental protection measures regarding industrial emissions and tightened regulations for air pollution led to the selection of wet scrubber to foundry units. Venturi scrubbers are compact and comparatively inexpensive to construct, but can be expensive to operate because they require high gas phase pressure drop to achieve high collection efficiency for small particles. Pressure drop is due to energy consumed as friction from gas flow, a loss that would occur even if no water were injected, and as energy to accelerate the droplets. Experiments were designed using Taguchi’s L16 orthogonal array to determine the best possible combination of geometrical parameters of convergent, throat and divergent sections of venturi scrubber. It is found that a combination of larger diameters and minimum length contributed to minimum pressure drop. However, the limiting velocity to improve the performance of venturi scrubber is to be identified using a CFD simulationdirection, atmospheric stability, local topography and air quality as such serious environmental effects such as acid deposition and forest decline can occur in a sensitive receiving environments or remote locations. Concern on the environmental and health effects of fine particles has lead to tightening of pollution control regulations word wide. Many applications that have provided adequate level of particle mass removal are now facing problems with fine and submicron particles.